Theoretical and experimental evaluation of LPG as refrigerant for domestic refrigerators and freezers - El-Awad, M.M.; Ahmed, Mirghani Ishak (IIUM Press, 2011)
The increasing concern about global wanning and depletion of the ozone layer has caused renewed interest in natural refrigerants for replacing synthetic refrigerants in household refrigeration and car air-conditioning applications. This study investigates the use of LPG, which is commonly available as cooking gas, as a replacement refrigerant for domestic retrigerators and freezers. A computer model, which evaluates the performance of hydrocarbon mixtures (propane and butane) as refrigerants, is used in this study to compare LPG with R134a. For given evaporator and condenser temperatures, the model computes the refrigeration effect, refrigerant mass and volume tlow rates, the compressor power input, COP, and compressor discharge temperature. The comparison is made on the basis of 1.0 KW of refrigeration capacity at different values of the evaporator temperature. The range considered for the evaporator temperature is typical to that usually met in domestic refrigerators and freezers. The paper also reports the results of a test comparing the performance of LPG with that of R134a on an educational test rig.